Fabrication of bio-inspired deterministic surfaces by photochemical machining for tribological applications. (October 2020) - Sánchez, J.C.; Toro, A.; Estupiñán, H.A.; Leighton, G.J.T.; Endrino, J.L.
Abstract: Surface texturing of AISI 52100 steel was carried out by photochemical machining. The geometrical parameters of the textured patterns were inspired by the characteristics of the skin of Vipera Ammodytes snake. The influence of the etching time and the size of the features on the quality of the textured surfaces was studied, as well as the effect of chemical modification on the surfaces etched by photochemical machining. The textured surfaces were tested in a pin-on-disc tribometer to evaluate the frictional response of the deterministic surfaces in comparison to stochastic surfaces. The results showed a marked influence of the etching time on the size and shape of the texture features, as well as a correlation between the coefficient of friction and the apparent contact area of the texture patterns. Also, a reduction of coefficient of friction was observed due to the deposition of WS2 and Graphite coatings onto the textured surfaces. Highlights: The Photochemical Machining process has not been used before for texturing AISI 52100 steel with a high resolution for small features. The fabricated bio-deterministic surfaces on sliding surfaces improved the tribological performances up to 30%. The coatings applied on the texturized surfaces improved the COF response under sliding condition. Useful information is provided by this study for non-conventional manufacture process applications on mechanical components.